Meteorin-Like Protein Reduces Oxidative Damage in Diabetic Mice - Yuksel, Furkan; Tekin, Suat; Ozcan, Mete; Tekin, Cigdem (Wiley, 2023)
[Abstract Not Available]
Keywords: Metrnl; Diabetes; Reactive Oxygen Species; Antioxidant; Oxidative Stress